STUDI KINETIKA DAN KINERJA FOTODEGRADASI METILEN BIRU OLEH KOMPOSIT TIO2/ELECTROCHEMICALLY EXFOLIATED GRAPHENE - Fatya, Alvian Ikhsanul; Raihan, Akhmad (UIN AR-RANIRY, 2025)
Methylene blue (MB) is a persistent cationic dye that contributes to water pollution due to its high chemical stability and resistance to natural degradation. This study aims to evaluate and compare the photocatalytic degradation performance and kinetic behavior of TiO2/electrochemically exfoliated graphene (TiO2/EEG) and TiO2 pigment under direct sunlight irradiation. The TiO2/EEG composite was synthesized through a simple direct-mixing method, chosen for its practicality and ability to facilitate effective interfacial contact between TiO2 and EEG. FTIR analysis confirmed the presence of O–H, C–O, and Ti–O–C functional groups, indicating chemical interactions between TiO2 and EEG. Photocatalytic degradation was monitored using UV–Vis spectroscopy over a 0–75 minutes irradiation period. After 60 minutes, TiO2/EEG degraded 78.55% of MB, whereas TiO₂ achieved 32.51%. The degradation followed a pseudo–first-order kinetic model, with rate constants of 0.01575 min⁻¹ for TiO2/EEG and 0.00342 min⁻¹ for TiO2, demonstrating that the composite accelerates MB degradation approximately five times faster. This enhancement is attributed to improved charge separation, higher adsorption capacity, and more efficient electron transfer facilitated by EEG. Although sunlight intensity was not controlled, the substantial performance gap confirms the potential of TiO2/EEG as an efficient, sunlight-driven photocatalyst for sustainable wastewater treatment